2021
DOI: 10.32394/pe.75.24
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depression, anxiety and stress in nurses working in Iranian hospitals: A systematic review and meta-analysis

Abstract: INTRODUCTION. Depression, anxiety, and stress are common problems among nurses. OBJECTIVE. This meta-analysis was conducted to investigate the prevalence of depression, anxiety, and stress among nurses working in Iranian hospitals. MATERIALS AND METHODS. Published studies on nurses working in Iranian hospitals were investigated in this meta-analysis. All national and international online databases, including Web of Science, PubMed, Scopus, Embase, Cochrane Library, Scientific Information Database (SID), MagIra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It was also expected based on earlier studies that the unique association of CDS with ADHD-HI would be negative in the regression analysis (i.e., higher scores on CDS would be associated with lower scores on ADHD-HI after controlling for the overlap of CDS and ADHD-IN). For anxiety and stress, given the high overlap between symptoms of depression, anxiety, and stress, at least among clinical samples other than individuals with CDS and ADHD [42][43][44], we expected that CDS would have a stronger correlation and unique association (partial regression coefficient) with anxiety and stress than ADHD-IN.…”
Section: The Present Studymentioning
confidence: 99%
“…It was also expected based on earlier studies that the unique association of CDS with ADHD-HI would be negative in the regression analysis (i.e., higher scores on CDS would be associated with lower scores on ADHD-HI after controlling for the overlap of CDS and ADHD-IN). For anxiety and stress, given the high overlap between symptoms of depression, anxiety, and stress, at least among clinical samples other than individuals with CDS and ADHD [42][43][44], we expected that CDS would have a stronger correlation and unique association (partial regression coefficient) with anxiety and stress than ADHD-IN.…”
Section: The Present Studymentioning
confidence: 99%
“…The review highlighted significant variability in reported prevalence of depressive symptoms among nurses, which underscores the impact of assessment tools on reported rates. (20) In comparison to the prevalence estimates of depressive disorders among the general population in Egypt (5.5%) as reported by the Global Burden of Disease study (2019), (3) the current rate of moderate/ severe depressive symptoms among psychiatric nurses (8.8%) indicates a higher magnitude of the problem among this sector of healthcare professionals. Regarding gender difference, Cheung and Yip (2016) found that female nurses had higher prevalence of depressive symptoms than male nurses (36.6% vs. 30.3% respectively), while moderate/ severe depression was nearly equal among them (23.7% vs. 23.6% respectively), and gender was not found to be a significant predictor for depressive symptoms.…”
Section: Discussionmentioning
confidence: 78%
“…In a more recent Egyptian study conducted by Ahmed et al, (2024) among psychiatric nurses in Sharkia Governorate reported that 66% of the studied nurses had depressive symptoms, where those mild/ moderate depression represented 48%, and 18% of nurses had severe depressive symptoms using BDI. (12) A recent systematic meta-analytic review of Iranian studies assessing prevalence of depression among nurses, conducted by Hemmati et al (2021), found that the prevalence of moderate/ severe depression was 36% according to the BDI, 28%, according to Depression Anxiety Stress Scales-21, and 52% according to General Health Questionnaire-28. The review highlighted significant variability in reported prevalence of depressive symptoms among nurses, which underscores the impact of assessment tools on reported rates.…”
Section: Discussionmentioning
confidence: 99%
“…Shift work rotation, frequent contact of disinfectants, workplace bullying and other physical or psychological factors that affect health are often challenges they are facing at work (Dumas et al, 2021;James et al, 2021;Shorey & Wong, 2021;Yang et al, 2022). Studies have shown that the incidence of depression among nurses ranged from 27.7% to 52.5% which was as high as the prevalence of hypertension and hyperlipidemia (Alkebsi et al, 2018;Chang et al, 2011;Hemmati et al, 2021;Kim et al, 2017;Zheng et al, 2021). All of these health issues among nurses are associated with the deterioration of quality of care and poor patient outcomes (Brešan et al, 2021;Kritsotakis et al, 2022).…”
Section: Backg Rou N Dmentioning
confidence: 99%